Comparing outcomes of nonoperative treatment for adhesive small bowel obstruction with and without antibiotics. Issue 5 (May 2021) - Konishi, Takaaki; Fujiogi, Michimasa; Michihata, Nobuaki; Morita, Kojiro; Matsui, Hiroki; Fushimi, Kiyohide; Tanabe, Masahiko; Seto, Yasuyuki; Yasunaga, Hideo
Abstract: Introduction: Some clinicians administer antibiotics in adhesive SBO treatment to prevent bacterial translocation without evidence confirming reduced sepsis and mortality. We aimed to evaluate the effectiveness of preventive antibiotic administration in nonoperative treatment of adhesive small bowel obstruction (SBO) in a retrospective study. Methods: Using a Japanese national inpatient database, we identified 114, 786 eligible patients with adhesive SBO and divided patients into a group who did not receive intravenous antibiotics in the initial 2 consecutive days after admission (control group, n = 71, 666) and a group who received intravenous antibiotics ≥2 days after admission (antibiotic group, n = 43, 120). To compare the in-hospital mortality, occurrence of sepsis, septic shock, Clostridioides difficile colitis, length of stay, and total costs between the two groups, we performed instrumental variable analyses to adjust for measured and unmeasured confounding factors. Results: Overall, in-hospital mortality was 2.2%, and the occurrence of sepsis was 0.8%. In the instrumental variable analyses, no significant differences were found for in-hospital mortality, occurrence of sepsis, septic shock, Clostridioides difficile colitis, or total hospitalization costs. The antibiotic group showed a longer length of stay than the control group (coefficient, 1.9 days; 95% confidence interval, 0.6–3.2). Conclusions: In this large nationwide cohort of patients with adhesive SBO, we found no benefit regarding preventive antibiotic administration in nonoperative treatment; however, antibiotic administration was associated with a longer hospital stay. These results did not support routine administration of antibiotics at admission to prevent bacterial translocation.